Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.immuni.2019.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome Regulates Hematopoiesis through Cleavage of the Master Erythroid Transcription Factor GATA1

Abstract: SUMMARY Chronic inflammatory diseases are associated with altered hematopoiesis that could result in neutrophilia and anemia. Here we report that genetic or chemical manipulation of different inflammasome components altered the differentiation of hematopoietic stem and progenitor cells (HSPC) in zebrafish. Although the inflammasome was dispensable for the emergence of HSPC, it was intrinsically required for their myeloid differentiation. In addition, Gata1 transcript and protein amounts increased in inflammaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 85 publications
3
72
0
Order By: Relevance
“…In addition, the same study showed that the cleavage of GATA1 by caspase 1 was required for the final steps of hemin‐induced erythroid differentiation in K562 cells, thus pointing at an additional mechanism whereby the inflammasome could regulate erythropoiesis through GATA1. Importantly, just like for caspase 3, GATA1 was indeed shown to be a substrate for cleavage by caspase 1 in vitro …”
Section: Caspase‐mediated Gata1 Protein Cleavage and Terminal Erythromentioning
confidence: 88%
See 3 more Smart Citations
“…In addition, the same study showed that the cleavage of GATA1 by caspase 1 was required for the final steps of hemin‐induced erythroid differentiation in K562 cells, thus pointing at an additional mechanism whereby the inflammasome could regulate erythropoiesis through GATA1. Importantly, just like for caspase 3, GATA1 was indeed shown to be a substrate for cleavage by caspase 1 in vitro …”
Section: Caspase‐mediated Gata1 Protein Cleavage and Terminal Erythromentioning
confidence: 88%
“…A recent study uncovered an additional caspase‐mediated mechanism for regulating GATA1 protein levels in hematopoiesis . Inflammasome activation in HSCs due to infection, led to caspase 1 activation and GATA1 cleavage and degradation, thus biasing cell fate decisions toward the myeloid lineage.…”
Section: Caspase‐mediated Gata1 Protein Cleavage and Terminal Erythromentioning
confidence: 99%
See 2 more Smart Citations
“…In order to ensure that this production of IL-18 was dependent on caspase-1, M1 MDMs were treated with VX-765, a caspase-1 specific inhibitor [2527], prior to either infection with HSV-1 or treatment with nigericin and LPS. IL-18 levels in cell supernatants were reduced to levels not significantly different than background in the presence of VX-765, suggesting that this IL-18 production is due to canonical caspase-1 activation ( Fig.…”
Section: Resultsmentioning
confidence: 99%